PENINGKATAN PEREKONOMIAN HASIL PRODUKSI KERUPUK IKAN BANDENG MELALUI PEMASARAN E-COMMERCE DI DESA KUALA LEUEGE PEREULAK ACEH TIMUR - Rahmatul Fajri; Ulil Amna; Fajriani Fajriani; Afrahun Naziah; Fitriani Fitriani; Yulida Amri; Rachmad Almi Putra; Beni Al Fajar (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2023)
The community service that has been carried out aims to improve the economy of the Kuala Leuge Pereulak village community in East Aceh through marketing local community products with e-commerse marketing techniques. The method of implementing the service carried out is through socialization or education regarding the effective use of marine products through the production of milkfish crackers which are marketed e-commerse. The results of the service activities that have been carried out have a positive impact on the community in Kuala Leuge village, namely being able to increase community creativity in processing existing resources to improve the economy, not only that through training from activities carried out by the community it is easier to market production results online in e-commerce. From the results of the activities carried out, it shows that there is an increase in the number of products sold every month.